(untitled) (Eurasian Scientific Herald, 2022)
This article is devoted to a linguistic analysis of the text of the essay of the modern Korean writer and Kyu MO, in order to determine the main features of the use of the artistic administration of the antithesis. In Korean, in the meaning of the opposite or, as is often believed, in the conceptosphere “opposite”, a significant influence of Confucianism on the worldview and mentality of the Koreans and its deep penetration into their consciousness and language is found. Studies on the theory of logical and linguistic specificity of antonymy have an important value due to the possibility of establishing the most general properties of this linguistic universe. The study of its implementation in the Korean language allows us to identify special methods of expression of the opposite characteristic of the Korean mental picture of the world. The antonymic meaning in the concept sphere “opposite” plays a large role in the transmission of certain meanings, it is in speech that the most diverse objects and concepts and the corresponding words can be opposed